Non-lyrical democracy: a rhetorical analysis of Miles Davis' Kind of Blue - Stewart, Neal Edward (Kansas State University, 2008)
On August 17, 1959 a jazz album entitled Kind of Blue hit record store shelves nationwide and changed the music forever. Recorded by the Miles Davis Sextet, the album popularly introduced a new sound, modal jazz, and has become one of the best selling jazz records of all time. A week after the release, following a concert promoting the album at the Birdland in New York, Davis was walking a white female friend to a taxi when he was stopped by a policeman. The officer told Davis to move along, and the two exchanged a few words and looks before the cop clubbed Davis over the head and arrested him. Davis was released shortly, but this incident is illustrative of a time in history where African-American music was embraced while the people themselves were treated as second-class citizens. This study explores rhetorical connections between jazz music and American democracy as it existed during the late 1950s. Using Sellnow & Sellnow's (2001) 'Illusion of Life' Rhetorical Perspective, this study analyzes the music of Kind of Blue as it connects with the political upheaval of the Civil Rights Movement. It concludes that the incongruity between the political and social tension of the country and the relatively laid-back sound of the music correlates with the non-violent resistance strategies used in the Movement. Implications are drawn about Sellnow & Sellnow's (2001) methodology, jazz music's potential in promoting/maintaining an inclusive democracy, and areas for future study.
Keywords: rhetoric; music; jazz; democracy; Music (0413); Speech Communication (0459)